Relationship between the severity of β-thalassaemia syndromes and the number of alleviating mutations - (:unkn) unknown (Blackwell Publishing Ltd, 1997)
Thalassaemia intermedia, defined as homozygous β-thalassaemia in which patients are not transfusion-dependent, covers a wide range of clinical severity. It may arise because one or more genetic factors ameliorate the otherwise severe phenotype of thalassaemia major. Exactly which and how many such mutations are necessary to produce a thalassaemia intermedia phenotype is in completely understood, although such information would be useful both clinically and for prenatal diagnosis. We examined DNA from 28 patients with thalassaemia intermedia resident in London and 28 matched patients with thalassaemia major, for 3 types of genetic modifying factors, namely; mild β-thalassaemia mutations, the upstream XmnI G-gamma globin gene polymorphism, and α-globin gene deletions. The results show that the number of alleviating mutations present has a large influence on the phenotype of patients with homozygous β-thalassaemias. A single alleviating mutation was present in 56% of thalassaemia intermedia subjects compared with 26% of thalassaemia major subjects. Two alleviating mutations were present in 33% of thalassaemia intermedia subjects compared with 1 thalassaemia major subject. No patients with thalassaemia major had 3 alleviating mutations, in contrast to 11% of those with thalassaemia intermedia. Although the findings did not account for the full range of phenotypic variation, such information is of potential value both in the clinical management and the prenatal diagnosis of homozygous β-thalassaemia.
Keywords: genotype/phenotype; thalassaemia intermedia; thalassaemia major